Managing people in changing organizations - Martin, Graeme (London Routledge Taylor & Francis group, 2025)
Managing People and Organizations in Changing Contexts addresses the contemporary problems faced by managers in dealing with people, organizations and change in a theoretically-informed and practical way. It does so by drawing on classic studies in management, up-to-date research (including the author's own), case studies, and reflective exercises. This textbook approaches people management and organizational development from the perspective of practising and aspiring managers, making it a valuable alternative to existing texts on organizational behaviour, change management, and human resource management.